Kathy Jacobs on PowerPoint - Jacobs, Kathy, 1962- (Holy Macro! Books, 2004)
A recognized expert in teaching Microsoft PowerPoint skills demonstrates how to design presentations to meet the needs of every audience. The peskiest PowerPoint problems are investigated, saving to removable media, how to back save, fast saves and other presentation corruptors, the AutoFormat feature, video drivers, hardware acceleration, and missing slide content. Also detailed is how to use PowerPoint for informational kiosks, games, and web sites. Tips for creating reports and graphical essays and for using PowerPoint with other products in the Microsoft Office suite are provided.